KAJIAN OPERASIONAL PINTU AIR DAERAH IRIGASI (D.I) SUNGAI DAHAN DESA NANGA NUAK KECAMATAN ELLA HILIR KABUPATEN MELAWI - Novenia; ANGGRAINI, IKA MUTHYA; zainal (Jurnal Teknologi Infrastruktur, 2023)
Irrigation area (D.I) Sungai Dahan, Nanga Nuak Village, Ella Hilir District, Melawi Regency with an area of ​​145 hectares which was first developed since ±1970 in the agricultural sector which focuses on rice crops. This research aims to obtain the amount of water needed and plan the operation of water gates in the Sungai Dahan Irrigation Area (D.I) Nanga Nuak Village, Ella Hilir District, Melawi Regency. Data analysis was carried out to obtain water requirements for rice plants, drainage modulus, and analysis of water gates using hydrological data. From the processing data, it was obtained that the need for irrigation water with the rice-padi-pawija cropping pattern was taken as an example of land processing, for calculating the need for irrigation water (DR) the maximum value was obtained at 0.149 l/sec/ha in October of the first planting period, while for the minimum value obtained at 0.00 l/s/ha in May and December in both planting periods, which means water is needed due to the lack of rainfall. The calculation of the water level in the upstream section and the height of the gate openings can be analyzed that at the water level in the upstream section of 0 the gate located at sluice gate 1 (P1) cannot be opened, the sluice gate can operate at the opening at sluice gate P2 to sluice gate P6 because there is a water level as high as 0.11m (P2) and a door opening height as high as 0.06m. At sluice gate 3, for the upstream water level as high as 0.21 m, an opening is made 0.17 m high gate which is intended to keep water sufficient for agricultural land.